2017
DOI: 10.1001/jamacardio.2017.0283
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcomes of Admission for Delivery in Women With Congenital Heart Disease

Abstract: In this study of hospital admissions for delivery in California, CHD was associated with incident CHF, atrial arrhythmias, and fetal growth restriction and complex CHD was associated with ventricular arrhythmias and maternal in-hospital mortality, although these outcomes were rare, even in women with complex CHD. These findings may guide monitoring decisions and risk assessment for pregnant women with CHD at the time of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
62
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 40 publications
4
62
1
3
Order By: Relevance
“…Increasing pregnancy numbers and rates among women with CHD have also been found in population‐based studies in the United States, and this could be due to several factors . First, the fact that more patients with CHD are known to survive to reproductive age may explain the increase in absolute pregnancy numbers .…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Increasing pregnancy numbers and rates among women with CHD have also been found in population‐based studies in the United States, and this could be due to several factors . First, the fact that more patients with CHD are known to survive to reproductive age may explain the increase in absolute pregnancy numbers .…”
Section: Discussionmentioning
confidence: 85%
“…Women with CHD had more cesarean deliveries than those without. Several other investigators have also found higher cesarean section rates among women with CHD when compared to pregnant controls . This trend may have further progressed since the cesarean delivery rates within the National Inpatient Sample in the United States from 2000 through 2010 were 40.7% (95% CI [39.7, 41.6]) and 32.3% (95% CI [32.2, 32.3]) among women with and without CHD, respectively .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations